The Urgency of Understanding Maqashid Al-Syariah In the Musyarakah Mutanaqishah Contract - Mugni Muhit (Journal of International Islamic Business Studies, 2024)
From the standpoint of maqasid sharia, this study aims to investigate whether it is urgent to implement the musyarakah mutanaqishah contract in Islamic banking in Indonesia. This study collects data using a descriptive qualitative technique with documentation. Secondary information on sharia standards, legislative provisions, operational requirements for sharia banking, sharia fatwas, operational and implementation standards, and research findings pertinent to the topic of discussion were utilised in this study. The data is then analyzed inductively. Analysis of the urgency of understanding maqasyid sharia in applying the musyarakah mutanaqishah contract. The results of the study found that the importance of understanding maqasyid sharia in a musyarakah mutanaqishah contract is necessary, considering that the spirit of msyarakah mutanaqisyah is rukhshah as a form of relief, while Islam always encourages lightening the burdens of others in a way that is mutual profit and loss sharing. From the perspective of risk imposition and equitable cooperation, this is also seen to be an alternative to mudharabah financing in Islamic banking, although it is not in conformity with the maqashid sharia and the regulations that have so far been in place in Indonesia